Tingkat Pengetahuan Dan Sikap Masyarakat Tentang Penyakit Kecacingan Berpengaruh Terhadap Kejadian Penyakit Kecacingan - Saidatina Hadijah; Abdul Khair; Noraida Noraida (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2021)
Worm disease is an infectious disease caused by parasites in the form of worms. The cause is soil-transmitted helminthiases (STH), which are intestinal worms that are transmitted to humans through soil contaminated by feces. STH infection can cause people to experience malnutrition. Severe infections can interfere with physical growth and cognitive development of sufferers. The purpose of this study was to determine the correlation between the level of knowledge and people's attitudes about helminthiasis with helminthiasis. This type of research was analytic with the research design using the case control method. The sample in this study was 38 respondents consisting of 19 people with helminthiasis and 19 did not suffer from helminthiasis. Data analysis using chi-square test. Chi-square test results showed the p-value for the correlation of the variable level of knowledge of 0,312> alpha (0,05) and the correlation of the attitude variable of 0,501> alpha (0,05) it can be stated that there is no relationship between the level of knowledge and attitudes of the community about the disease helminthiasis with the incidence of helminthiasis in the working area of cempaka puskesmas. If this research is to be continued, in order to be better, then the research sample should be expanded and other possible factors become one of the causes of STH infection such as clean and healthy life behavior, latrine quality, water quality, soil quality and others.